Reconstruction of the esophagus with left transverse colon: Esophagus - intrathoracic coloplasty, in a case of esophageal atresia with widely separated esophageal strands - Lattaro, Diver; Chizzola, Manlio; Marx, Martín; Sbárbaro, Orester; Leautier, Gastón (Cirugía del Uruguay, 1979)
In a case of atresia of esophagus, with widely separated ends, the patient was cured after a series of successive operations consisting in esophagocoloplastia with left transverse colon (retro - gastric, left trans - diaphragmatic - parahiatal and transpleural, behind the hilus of lung) and inferior anastomosis of transplant to the gastric cupufa and not to the inferior esophageal stump which is small and becomes atrophic after 18 months, while the colon has a large caliber; it is also preferable that the suture be sub - diaphragmatic and not mediastinal in case it fails. Upper anastomosis was left extra - thoracic cervical.